Explanation: The given expression is: 70 - 3g This means that we are removing 3g from 70. As the value of g increases, the value of 3g will also increase. This means that the amount we remove from the 70 will also increase which will lead to a decrease in the value of the expression.
Examples: At g = 1: 70 - 3g = 70 - 3(1) = 70 - 3 = 67 At g = 2: 70 - 3g = 70 - 3(2) = 70 - 6 = 64 At g = 3: 70 - 3g = 70 - 3(3) = 70 - 9 = 61 At g = 4: 70 - 3g = 70 - 3(4) = 70 - 12 = 58
We can note that as g increases by 1, the value of the expression decreases by 3.